2011
DOI: 10.1088/0022-3727/44/34/345203
|View full text |Cite
|
Sign up to set email alerts
|

Sub-60 °C atmospheric helium–water plasma jets: modes, electron heating and downstream reaction chemistry

Abstract: To cite this version:J J Liu, M G Kong. Sub-60°C atmospheric heliumwater plasma jets: modes, electron heating and downstream reaction chemistry. Journal of Physics D: Applied Physics, IOP Publishing, 2011, 44 (34) AbstractFor plasma treatment of many heat labile materials (e.g. living tissues) that are either moist or contain a surface layer of liquid, it is desirable that the gas plasma is generated at atmospheric pressure for process convenience and with a gas temperature ideally no more than 60 o C for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…Effectively, these results reveal a previously unknown dimension of varying plasma chemistry. It is worth noting that with this paper, chaos has been observed in low-temperature atmospheric plasma jets in helium mixture with both oxygen [14,15] and water vapor [13]. It is conceivable that it may exist in atmospheric plasmas in other gas mixtures and indeed other electrode configurations.…”
Section: Impact On Chemistrymentioning
confidence: 59%
See 2 more Smart Citations
“…Effectively, these results reveal a previously unknown dimension of varying plasma chemistry. It is worth noting that with this paper, chaos has been observed in low-temperature atmospheric plasma jets in helium mixture with both oxygen [14,15] and water vapor [13]. It is conceivable that it may exist in atmospheric plasmas in other gas mixtures and indeed other electrode configurations.…”
Section: Impact On Chemistrymentioning
confidence: 59%
“…A key advantage of the DBD jet configuration is that the reactive species generated in the capillary are effectively transported to a downstream sample where they are able to interact without compromising the stability of the device [11,12]. Depending on dissipated electric power, these atmospheric plasmas have been shown to operate in different modes including Townsend, glow and nonthermal arc modes, all modulated at the driving frequency [13]. Recently, however, it has been reported that atmospheric-pressure plasma jets can exhibit chaotic behavior under certain conditions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the plasma is susceptible to instabilities and transition to arc or spark when small changes in electrical properties occur. Distinct modes have been reported for RF-APPJs, where mode transitions can occur via the sheath breakdown events associated with secondary electron emission from the electrode surface [34][35][36]. Mode transitions can lead to high current densities and negative differential conductivity, resulting in instabilities and arc-like behavior that can inflict damage on the target substrate [37,38].…”
Section: Model-based Feedback Control For Appjsmentioning
confidence: 99%
“…[10][11][12] Recently, more complex temporal nonlinear behaviors of APGD, such as period-doubling bifurcation and chaos, have been frequently observed in both experiments and numerical simulations. [13][14][15][16][17][18][19] Different from the single period discharge, the current pulses in period-doubling and chaos discharges repeat at multiple applied voltage cycles or fluctuate stochastically. These nonlinear behaviors are sensitive to discharge parameters and can be caused by the fluctuations of a variety of control parameters, such as the driving frequency, voltage amplitude, and gap width.…”
Section: Introductionmentioning
confidence: 99%